Pelayanan Lifeguard Balawista di Pantai Kuta Bali - Goesmayanti, Fitrie (STBA Yapari-ABA Bandung, 2011)
Kuta Beach is the most famous tourist destination in Bali. People from all over the world come to Kuta Beach for sunbathing on the white sand, watching the sunset, swimming, and surfing. Sometimes people are too excited in doing water activities, and Kuta Beach is not a risk-free tourist object. Every water activity might cause accident, injury, or even death. Therefore, the supervision of Balawista Kuta as a lifeguard team is very important for preventing unexpected water accident in the area of Kuta Beach.